Immigration, trade and productivity in services: Evidence from U.K. firms - Gianmarco I. P. Ottaviano; Giovanni Peri; Greg C. Wright (Goethe University Frankfurt, Center for Financial Studies (CFS), 2016)
This paper explores the impact of immigrants on the imports, exports and productivity of service- producing firms in the U.K. Immigrants may substitute for imported intermediate inputs (offshore production) and they may impact the productivity of the firm as well as its export behavior. The first effect can be understood as the re-assignment of offshore productive tasks to immigrant workers. The second can be seen as a productivity or cost cutting effect due to immigration, and the third as the effect of immigrants on specific bilateral trade costs. We test the predictions of our model using differences in immigrant inflows across U.K. labor markets, instrumented with an enclave-based instrument that distinguishes between aggregate and bilateral immigration, as well as immigrant diversity. We find that immigrants increase overall productivity in service-producing firms, revealing a cost cutting impact on these firms. Immigrants also reduce the extent of country-specific offshoring, consistent with a reallocation of tasks and, finally, they increase country-specific exports, implying an important role in reducing communication and trade costs for services.
urn:nbn:de:hebis:30:3-424199
Keywords: F16; F10; F22; F23; 330; Immigration; Services Trade